Impaired eye tracking is associated with symptom severity but not dynamic postural control in adolescents following concussion - Jessie R. Oldham; William P. Meehan, III; David R. Howell (Elsevier, 2021)
Purpose: The purpose of the study was to (1) examine the relationship between self-reported symptoms and concussion-related eye tracking impairments, and (2) compare gait performance between (a) adolescents with a concussion who have normal eye tracking, (b) adolescents with a concussion who have abnormal eye tracking, and (c) healthy controls. Methods: A total of 30 concussed participants (age: 14.4 ± 2.2 years, mean ± SD, 50% female) and 30 controls (age: 14.2 ± 2.2 years, 47% female) completed eye tracking and gait assessments. The BOX score is a metric of pupillary disconjugacy, with scores <10 classified as normal and ≥10 abnormal. Symptoms were collected using the Post-Concussion Symptom Scale (PCSS), and gait speed was measured with triaxial inertial measurement units. We conducted a linear regression to examine the relationship between PCSS and BOX scores and a two-way mixed effects analysis of variance to examine the effect of group (abnormal BOX, normal BOX, and healthy control) on single- and dual-task gait speed. Results: There was a significant association between total PCSS score and BOX score in the concussion group (β = 0.16, p = 0.004, 95% confidence interval (95%CI): 0.06‒0.27), but not in the control group (β = 0.21, p = 0.08, 95%CI: -0.03 to 0.45). There were no significant associations between PCSS symptom profiles and BOX scores in the concussion or control groups. There were also no significant differences in single-task (Abnormal: 1.00 ± 0.14 m/s; Normal: 1.11 ± 0.21 m/s; Healthy: 1.14 ± 0.18 m/s; p = 0.08) or dual-task (Abnormal: 0.77 ± 0.15 m/s; Normal: 0.84 ± 0.21 m/s; Healthy: 0.90 ± 0.18 m/s; p = 0.16) gait speed. Conclusion: The concussed group with impaired eye tracking reported higher total symptom severity, as well as worse symptom severity across the 5 PCSS symptom domain profiles. However, eye tracking deficits did not appear to be driven by any particular symptom domain. While not statistically significant, the slower gait speeds in those with abnormal BOX scores may still be clinically relevant since gait-related impairments may persist beyond clinical recovery.